IN VIVO EFFECT OF GUIDING-HERB RADIX PLATYCODONIS AND RADIX CYATHULAE ON PAEONIFLORIN PHARMACOKINETICS OF XUEFU ZHUYU TANG IN RATS - Tang, Song-qi; Chen, Yun-hui; Chen, Xi-ping; Zhang, Xiao-dan; Huang, Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Xuefu Zhuyu Tang (XFZYT), first recorded in Correction of Errors in Medical Works by Qing-ren Wang, has been proven reliable and effective for curing various diseases such as atherosclerosis, hypertension, hyperlipidemia, and angina pectoris. It consists of 11 herbs and two of them, Radix platycodonis and Radix cyathulae, have been traditionally considered as guiding herbs and deeply valued by tens of millions of Chinese medicine practitioners. Do Radix platycodonis and Radix cyathulae affect the pharmacokinetics of the effective constituent-paeoniflorin of XFZYT? If yes, in what way? This study aims to answer these questions. Materials and Methods: The medicinal solutions of XFZYT, XFZYT without Radix platycodonis (XFZYT-JG), XFZYT without Radix cyathulae (XFZYT-NX), and XFZYT without Radix platycodonis and Radix cyathulae (XFZYT-JG-NX) were prepared and administrated to rats in the normal group and the blood-stasis model group by gavage, respectively. The blood samples of rats in the normal group were obtained 5, 10, 15, 20, 30, 45, 60, 120, and 240 minutes after gavage; whereas the blood samples of rats in the blood-stasis model group were obtained 10, 15, 20, 30, 45, 90, 150, and 240 minutes after gavage. Biological samples were processed; the assays of specificity, precision, linearity, intra-day and inter-day precisions, recovery and stability were conducted; high performance liquid chromatography was performed to detect paeoniflorin content; and DAS software was adopted to generate pharmacokinetic parameters. Mobile phase was composed of acetonitrile and water (16:84), detection wavelength was 230 nm, and riboflavin was set as internal standard substance.Results: The pharmacokinetic parameters of the rats in the normal group after oral gavage of XFZYT, XFZYT-JG, XFZYT-NX, and XFZYT-JG-NX were Cmax = (0.363±0.248, 0.065±0.020, 0.099±0.033, 0.099±0.020) mg/L, Tmax = (0.276±0.084, 0.583±0.342, 0.555±0.228, 0.317±0.033)h, t1/2 = (0.501±0.241, 1.021±0.522, 0.853±0.377, 1.227±0.402) h; and AUC0-∞ = (0.381±0.415, 0.13±0.085, 0.166±0.066, 0.185±0.059) mg/L·h.; whereas the pharmacokinetic parameters for the rats in the blood-stasis model group after oral gavage of XFZYT, XFZYT-JG, XFZYT-NX, and XFZYT-JG-NX were Cmax = (0.315±0.153, 0.215±0.044, 0.228±0.056, 0.248±0.09) mg/L, Tmax = (0.5±0, 0.667±0.129, 0.5±0, 0.542±0.102) h, t1/2 = (0.408±0.146, 0.813±0.135, 0.708±0.383, 0.741±0.173) h, and AUC 0-∞ = (0.306±0.157, 0.408±0.136, 0.368±0.159, 0.381±0.246) mg/L·h. Conclusion: The guiding herbs, Radix platycodonis and Radix cyathulae, significantly increased the absorption amount and rate of paeoniflorin in XFZYT, and accelerated its elimination from the blood.